Tranexamic acid in pediatric combat trauma requiring massive transfusions and mortality. Issue 2 (August 2020) - Hamele, Mitchell; Aden, James K.; Borgman, Matthew A.
Abstract : BACKGROUND: Tranexamic acid (TXA) has been demonstrated to decrease mortality in adult trauma, particularly in those with massive transfusions needs sustained in combat injury. Limited data are available for the efficacy of TXA in pediatric trauma patients outside of a single combat support hospital in Afghanistan. METHODS: The Department of Defense Trauma Registry was queried for trauma patients younger than 18 years from Iraq and Afghanistan requiring 40 mL/kg or greater of blood product within 24 hours of injury. Burns and fatal head traumas were excluded. Primary outcome was in-hospital mortality. Secondary outcomes were hospital, ventilator, and intensive care unit–free days, as well as total blood product volume. RESULTS: Among those pediatric patients receiving massive transfusions, those who received TXA were less likely to die in hospital (8.5% vs. 18.3%). Patients who received TXA and those who did not have similar hospital-free days (19 vs. 20), ventilator-free days (27 vs. 27), and intensive care unit–free days (25 vs. 24). Those who received TXA had higher 24-hour blood product administration (100 mL/kg vs. 75 mL/kg). None of our results rose to the level of statistical significance. The TXA administration significantly reduced odds of death on logistic regression (odds ratio, 0.35; 95% confidence interval, 0.123–0.995; p = 0.0488). CONCLUSION: Use of TXA in pediatric patients with combat trauma requiring massive transfusions trended toward a significant improvement in in-hospital mortality ( p = 0.055). This mortality benefit is similar to that seen in adult studies and a less well characterized cohort in another pediatric study suggesting TXA administration confers mortality benefit in massively transfused pediatric combat trauma victims. LEVEL OF EVIDENCE: Evidence (retrospective cohort), Level IV